PENGARUH PEMBELAJARAN AKTIF TIPE COLLABORATIVE LEARNING GROUPS TERHADAP PEMAHAMAN KONSEP DAN KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA PGSD STKIP MUHAMMADIYAH MUARA BUNGO - Mulza Rois; Nurlev Avana (Universitas Negeri Medan, 2020)
Abstract: The effect of active learning with Collaborative Learning Groups type on concept of understanding and mathematical communication skills of students in education of elementary school teacher (PGSD) at university of Muhammadiyah Muara Bungo. The ability of understanding mathematical concepts and communication skills was a math learning goals stated by the Ministry of Education, and was a very important aspect in learning mathematics. Lack of communication skills and understanding of mathematical concepts students will affect the quality of student learning that result in low student achievement in school, it was also happening in education of elementary school teacher (PGSD). Coperative learning group learning strategies was one alternative to improve the liveliness and creativity of students in learning.This research is a Quasi Experiment. The population in this study were students of education of elementary school teacher (PGSD). The samples in this study were students of class II E PGSD at university of Muhammadiyah Muara Bungo as experimental class and II D PGSD at university of Muhammadiyah Muara Bungo grade students as a class randomly selected controls. Instrument used was a written test. The data obtained were analyzed using test mann- whitney u.The results showed that the ability of understanding the overall concept and capable students who are taught by low initial learning activen learning higher than students taught with conventional learning, communication skills and capable overall high initial learning strategies taught by ctiven learning higher than the students who taught by conventional learning. Keywords: The effect of active learning with Collaborative Learning Groups, concept of understanding, mathematical communication skills Abstrak: Pengaruh pembelajaran aktif tipe Collaborative Learning Groups terhadap Pemahaman Konsep dan Kemampuan Komunikasi Matematis Mahasiswa PGSD STKIP Muhammadiyah Muara Bungo. Kemampuan pemahaman konsep matematika dan keterampilan komunikasi merupakan tujuan pembelajaran matematika yang ditetapkan oleh Kementerian Pendidikan dan merupakan aspek yang sangat penting dalam pembelajaran matematika. Kurangnya kemampuan komunikasi dan pemahaman konsep matematika mahasiswa akan mempengaruhi kualitas belajar mahasiswa yang berakibat pada rendahnya prestasi belajar mahasiswa PGSD. Strategi pembelajaran kelompok pembelajaran kooperatif merupakan salah satu alternatif untuk meningkatkan keaktifan dan kreativitas mahasiswa dalam belajar.Penelitian ini merupakan Quasi Experiment. Populasi dalam penelitian ini adalah mahasiswa PGSD. Sampel dalam penelitian ini adalah mahasiswa kelas II E PGSD STKIP Muhammadiyah Muara Bungo sebagai kelas eksperimen dan mahasiswa kelas II D PGSD Muhammadiyah Muara Bungo sebagai kelas kontrol yang dipilih secara acak. Instrumen yang digunakan adalah tes tertulis. Data yang diperoleh dianalisis menggunakan uji mann-whitney u.Hasil penelitian menunjukkan bahwa kemampuan pemahaman konsep secara keseluruhan dan kemampuan mahasiswa yang diajar dengan pembelajaran awal rendah keaktifan lebih tinggi dari pada mahasiswa yang diajar dengan pembelajaran konvensional, keterampilan komunikasi dan secara keseluruhan mampu secara keseluruhan kemampuan strategi pembelajaran awal tinggi yang diajar dengan pembelajaran aktif lebih tinggi dari pada mahasiswa yang diajar dengan pembelajaran konvensional. Kata Kunci: Pengaruh pembelajaran aktif tipe collaborative learning groups, Pemahaman Konsep dan Kemampuan Komunikasi Matematis.